NAC-1, a Rat Brain mRNA, Is Increased in the Nucleus Accumbens Three Weeks after Chronic Cocaine Self-Administration - Cha, Xian-Yuan (J Neurosci, 1997)
Chronic cocaine use leads to biochemical and behavioral changes that can persist for weeks to months after drug administration is discontinued. Alterations in gene expression in the mammalian CNS may contribute to these long-term neural consequences of cocaine abuse. A combined in situ transcription–PCR amplification strategy was used to isolate a novel mRNA, NAC-1, from the nucleus accumbens of rats 3 weeks after discontinuing 3 weeks of intravenous cocaine self-administration. In rats that self-administered cocaine, levels of NAC-1 were increased ∼50% in the nucleus accumbens but not in the dorsal striatum or hippocampus, when compared with levels from yoked-saline controls. In situ hybridization analysis demonstrated increased numbers of NAC-1-expressing cells in the nucleus accumbens of rats who had self-administered cocaine. NAC-1 mRNA exists as one form, ∼4400 nucleotides (nt) in size, and also is present at much lower amounts in non-neural tissues. A full-length cDNA clone was isolated from a whole brain library. The predicted polypeptide sequence contains a POZ domain in the first 120 amino acids; the same POZ domain sequence mediates protein–protein interactions among some transcriptional regulators. NAC-1 mRNA levels were also increased in the nucleus accumbens 1 week after 6 d of noncontingent cocaine treatments. Regulation of NAC-1 mRNA in the nucleus accumbens demonstrates a long-term effect of cocaine use on cellular function that may be relevant in behavioral sensitization or cocaine self-administration.